COMMUNITY-ACQUIRED PNEUMONIA COMPLICATED BY SEPSIS CAUSED BY KLEBSIELLA PNEUMONIAE: A CASE REPORT - A.V. Lavrenko (Проблеми екології та медицини, 2017)
The actuality of the problem of sepsis is currently determined by several causes: a significant frequency of the disease, high lethality and, consequently, significant economic damage caused by this disease in economically developed countries. The clinical picture is systematized and outlined, questions of laboratory diagnostics, the principles of treatment are defined. Analyzed pathological changes that occur in sepsis on the part of various organs and systems . Shown the diagnostic algorithm, which is acceptable both in the presence and in the absence of laboratory verification of the disease. Starting antibacterial therapy is recommended as an empirical therapy, depending on the localization of the primary focus and systemic manifestations of infection. Thus, considering the clinical case of sepsis, one should emphasize that it is important to collect detailed medical history (especially if broncho-pulmonary system is involved), to consider where the patient works and his/her profession (especially for health-care workers, and other categories of people who work with organized groups of population). It is advisable to assume a nosocomial infection as a pathogen.